2021
DOI: 10.1016/j.ajog.2020.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of response for elagolix with add-back therapy in women with heavy menstrual bleeding associated with uterine fibroids

Abstract: BACKGROUND: Uterine fibroids are one of the most common neoplasms found among women globally, with a prevalence of approximately 11 million women in the United States alone. The morbidity of this common disease is significant because it is the leading cause of hysterectomy and causes significant functional impairment for women of reproductive age. Factors including age, body mass index, race, ethnicity, menstrual blood loss, fibroid location, and uterine and fibroid volume influence the incidence of fibroids a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…This subset analysis in women with fibroids and coexisting adenomyosis showed that elagolix with add-back therapy resulted in better quality of life than did placebo on the basis of mean improvement from baseline to month 6 in symptom severity and health-related quality of life total scores. In fact, the symptom severity and health-related quality of life scores of the adenomyosis subset after elagolix with add-back treatment were consistent with the UFS-QOL scores validated in healthy women without fibroids (mean [standard deviation]: 22.5 [21.1] and 86.4 [17.7], respectively) ( 21 ). In addition, the mean changes in the scores from baseline to month 6 were considered clinically meaningful ( 21 ).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…This subset analysis in women with fibroids and coexisting adenomyosis showed that elagolix with add-back therapy resulted in better quality of life than did placebo on the basis of mean improvement from baseline to month 6 in symptom severity and health-related quality of life total scores. In fact, the symptom severity and health-related quality of life scores of the adenomyosis subset after elagolix with add-back treatment were consistent with the UFS-QOL scores validated in healthy women without fibroids (mean [standard deviation]: 22.5 [21.1] and 86.4 [17.7], respectively) ( 21 ). In addition, the mean changes in the scores from baseline to month 6 were considered clinically meaningful ( 21 ).…”
Section: Discussionsupporting
confidence: 71%
“…In fact, the symptom severity and health-related quality of life scores of the adenomyosis subset after elagolix with add-back treatment were consistent with the UFS-QOL scores validated in healthy women without fibroids (mean [standard deviation]: 22.5 [21.1] and 86.4 [17.7], respectively) ( 21 ). In addition, the mean changes in the scores from baseline to month 6 were considered clinically meaningful ( 21 ).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Al-Hendy and colleagues analyzed data from the Elaris UF-1 and UF-2 trials to see if the outcomes for elagolix with hormonal addback therapy demonstrated safety and efficacy in subgroups of patients of varying ages, races and ethnicities, baseline menstrual blood loss, body mass indices, fibroid location, and uterine and fibroid volume. 5 Results. In all subgroups, they found a statistically significant reduction in blood loss in mean menstrual blood loss volume for those treated with elagolix plus hormonal addback therapy compared with those treated with placebo.…”
Section: Effectiveness In Subgroupsmentioning
confidence: 99%
“…An additional data analysis from the same researchers assessed the effect of elagolix with hormonal add-back therapy in a number of patient subgroups. 5 These 3 publications have added to our knowledge of this therapy, and it is worth reviewing them in this context.…”
mentioning
confidence: 99%